Meningkatkan Kesadaran Hukum tentang Perkawinan Usia Anak serta Dampaknya Menuju Bonus Demografi di Kecamatan Ciwaringin, Kabupaten Cirebon - Harmono, Harmono; Suwarsono, Hendri; Abdulah Pakarti, Muhammad Husni (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
Child marriage is still a serious problem in Indonesia, including Cirebon Regency which records hundreds of marriage dispensation applications every year. This practice has a negative impact on children's rights, educational continuation, reproductive health, and the quality of human resources to deal with the demographic bonus. This Community Service activity aims to improve legal knowledge and reproductive health, change attitudes towards child marriage, and encourage the formation of an Anti-Child Marriage Village Forum in Ciwaringin District. The program will be carried out in July-September 2025 by involving 45 participants (teenagers, parents, community leaders, village cadres) through a participatory and collaborative approach. The stages include initial observation, training and workshops, project-based campaigns, village forum formation, and evaluation. Data were collected by pre-post questionnaires, observations, in-depth interviews, and photo/video documentation. The results of the evaluation showed a significant increase in legal knowledge (54.3 → 82.7), knowledge of reproductive health (48.5 → 79.1), and attitudes in support of child marriage postponement (61.2 → 83.9). The participation rate reached >90%, with the active involvement of PKK teenagers and mothers in the production of posters, leaflets, digital content, and the establishment of village forums through the Village Head Decree. This activity concluded that community-based reproductive health and legal education is effective in improving community knowledge and attitudes and triggering local leadership for child marriage prevention advocacy, although real behavioral change requires sustained cross-sectoral interventions.